REFLEKSI FALSAFAH AJARAN HIDUP MASYARAKAT JAWA DALAM PROSA LIRIK PENGAKUAN PARIYEM KARYA LINUS SURYADI - Ery Agus Kurnianto (Madah: Jurnal Bahasa dan Sastra, 2015)
Philosophy of life came up due to the existence of culture  that believed and upheld by people who own them. The Javanese philosophy existed in the culture that are believed by the Javanese community. The philosophy of Javanese community actualized in the characters in the novel Pengakuan Pariyem. The character in the novel Pengakuan Pariyem is one of the symbols of people who still uphold the existing culture in their society, that is Javanese. The study of sociology of literature was used to analyze novel Pengakuan Pariyem. Literature is a direct mirror of various social structures, kindship, and others. Therefore, it is the task of sociology of literature to correlate fictional characters and situations created by the author of the historical circumstances of its origins. The purpose of this study is to describe the value of Javanese philosophy of life contained in Unen-Unen in novel Pengakuan Pariyem written by Linus Suryadi. This study used a qualitative design. The results of the research showed that there are three basic principles which used as a basis of Javanese philosophy found in novels Pengakuan Pariyem. These three principles are (1) awareness in divinity, (2) awareness in universality, and (3) the awareness of human civilization.